Metoprolol Tartrate-An Ideal Drug Candidate for Transdermal Antihypertensive Therapy: It’s Preliminary Preformulation Screening - Bhowmick, Mithun; Tamizharasi, Sengodan; Dubey, Nitin; Rewanand Gaidhane, Kundan; Sivakumar, Thangavel (Asian Journal of Chemistry, 2012)
Metoprolol tartrate is the antihypertensive drugs that have been explored for its transdermal delivery potential in the present preliminary preformulation screening. Metoprolol tartrate is a selective adrenergic blocking agent, has become a widely used therapeutic agent for mild and moderate hypertension. Plasma elimination half-life (< 4 h), molecular weight (< 750) and poor bioavailability (40-60 %) due to extensive first pass metabolism, makes metoprolol tartrate a suitable candidate for transdermal drug delivery. However the transdermal route of administration cannot be employed for a large number of drugs therefore before going into the actual formulation of transdermal drug delivery system of metoprolol tartrate, other parameters has also been investigated in the present paper i.e., drug identification by advanced techniques like FTIR/ DSC, determination of lmax and plotting of calibration curve of the drug, physicochemical properties of the drug (solubility, melting point, partition coefficient log P), in vitro permeation study through porcine skin via determination of steady-state flux, permeability coefficient, diffusion coefficient, lag time and permeation enhancement study by permeation enhancers such as SLS, DMSO and oleic acid. The results suggested that metoprolol tartarate is the ideal drug for transdermal drug delivery system and SLS, DMSO and oleic acid induced a significant increase in drug permeation, with DMSO showing the highest enhancing effect at the lowest concentration (5 %) applied and hence may assist in the development of an effective transdermal formulation of metoprolol tartrate for use in humans.